Fisher and Shannon Functionals for Hyperbolic Diffusion - Cáceres, Manuel O. (2023)
The complexity measure for the distribution in space-time of a finite-velocity diffusionprocess is calculated. Numerical results are presented for the calculation of Fisher’s information,Shannon’s entropy, and the Cramér–Rao inequality, all of which are associated with a positivelynormalized solution to the telegrapher’s equation. In the framework of hyperbolic diffusion, thenon-local Fisher’s information with the x-parameter is related to the local Fisher’s information with thet-parameter. A perturbation theory is presented to calculate Shannon’s entropy of the telegrapher’sequation at long times, as well as a toy model to describe the system as an attenuated wave in theballistic regime (short times).